Experimental Revealing of Domains Appearing in n-GaAs in the Presence of Strong Microwave Fields - Miskinis, R.; Nekrasas, N.; Parseliunas, J.; Urba, E. (Elektronika ir Elektrotechnika, 1999)
A method for experimental revealing of domains, appearing in n-GaAs under strong microwave (MW) fields, is reported. The method employs electric fields of perpendicular directions. The investigations are carried out in the X-band, using epitaxial samples in which the free electron density n0=7.7x1015 cm-3. The results are qualitatively confirmed by numerical simulations. The data obtained imply that the process of domenization under strong MW fields can be employed for formation of pulses with fronts of subnanosecond duration.